Comparative Vertical Migration of Three Different Strains of Heterorhabditis bacteriophora and a Single Strain of Heterorhabditis megidis in Sand at 25°C - Csontos, Attila Sándor; Grewal, Parwinder S.; Klein, Michael G. (Acta Agraria Debreceniensis, 2003)
Heterorhabditis bacteriophora and Heterorhabditis megidis) were tested for downward migration in 9.5 cm vertical sand columns at 25°C with and without a larva of the wax moth, Galleria mellonella, at the bottom. The number of infective juveniles (IJs) in the upper section decreased since the IJs gradually migrated down toward the Galleria larvae into the lower section of the shell vials. Only the isolate OH 25 behaved differently, because the number of IJs decreased this isolate in the lower section. This isolate was the quickest, since after 12 hrs, most IJs could be found in the lower section of the vials from this isolate. The number of IJs was so small in the lower section that 12 hrs after injection, only the isolates MHG 3 and OH 25 could kill the Galleria larvae. Besides the fact that mortality occurred among the Galleria larvae with the above isolates, neither IJs nor adults could be detected in either living or dead Galleria larvae 12 hrs after IJ injection. It is noteworthy that the behavior of the isolate Megidis was different from the other isolates: the number of IJs was so negligible in the lower section of the vials that even after 36 hrs none of the Galleria died and, consequently, neither adults nor IJs could be detected after dissecting the Galleria larvae. Each isolate could reach the lower section of the vials, yet only the isolate Megidis could not infect and kill the host. After dissecting the larvae, most IJs and adults could be found in the isolate MHG 3 (95 IJs and adults altogether) 36 hrs after injection.